DEVELOPMENT OF ENTREPRENEURSHIP AND ATTRACTION OF INVESTMENTS THE MAIN FACTOR IN THE DEVELOPMENT OF UZBEKISTAN - Миркамол Мирсалиев (American Journals, 2023)
On May 10, 2023, the next annual conference of the Islamic Development Bank started its work in Jeddah, Saudi Arabia. This action every year held from measures be , then basically Islam development to the bank member from the states and other from countries guests , especially international ones and local finance institution and organizations participation they do. From Uzbekistan too commerce banks and another financial organizations representatives this at the event participation reach _ Gladly, ours commerce banks too this at the event reach during ( self-customers requirements according to that we think ) Islam development bank to the group incoming from organizations funds attraction to do according to contracts to sign.